CHALLENGES AND PERSPECTIVES OF THE QUALITY OF EDUCATION IN SMALL MUNICIPALITIES IN THE STATE OF AMAZONAS: ADAPTED TO THE SPECIFIC CONTEXT OF THE MUNICIPALITY OF TONANTINS - Aquiles Linhares Gouvea, German; Nascimento Martins, Gézimo; Nascimento Martins, Valdira; da Costa dos Santos, Sidney; dos Santos Cobos, Wilsinho; Penaforth Pinto, Emerson; Cobos dos Santos, Givanildo (Revista Gênero e Interdisciplinaridade, 2024)
This article presents a critical analysis of the challenges and perspectives of the quality of education in small municipalities in the State of Amazonas. Initially, the problems faced by Brazilian education are contextualized, with an emphasis on the importance of examining the quality of education in remote regions such as Alto Solimões. The literature review addresses fundamental concepts about education, highlighting the universality and complexity of the educational phenomenon. Next, the indicators and criteria used to evaluate the quality of education are discussed, adapted to the specific context of Tonantins, in Amazonas. Data analysis reveals the main challenges faced by education in this region, such as precarious infrastructure and a lack of qualified professionals. In addition, the prospects for improvement and ongoing initiatives to promote the quality of education are evaluated, such as continuing training programs for teachers and projects to improve school infrastructure. The survey results provide important insights into the obstacles and opportunities for improving education in these municipalities. Finally, implications for educational practice and suggestions for future research are discussed, highlighting the importance of local community involvement in educational management and the need for more effective and inclusive educational investments and policies in these remote regions.